Presenting possibilities, plans, pathways, programmes: NASA's use of strategic roadmapping visuals. Issue 5 (4th May 2023) - Kerr, Clive
ABSTRACT: Strategic roadmaps provide a visual approach for structuring long-term plans, conveying policy commitments, summarising an organisation's intent and depicting prospective pathways to realising a vision. When it comes to generating roadmaps and deploying them to enhance communication, NASA is the preeminent author and publisher of these purposeful visualisations. They have a breadth and depth of experience, consistently creating strategic roadmaps since the early 1960s, and have produced a rich array of various types spanning the spectrum of organisational/programme levels and administrative functions. In addition to highlighting notable examples published by NASA, a critique and contrast are made in respect of their presentational style, message design and narrative sequence, content and substance, diagrammatic structure, orientation and format.